New experimental possibilities for statin myopathy diagnosing - E. V. Vinogradova; Z. I. Mikashinowich; E. S. Belousova (Бюллетень сибирской медицины)
Aim. To identify the relationships between structural proteins of myocytes, as well as indicators of antioxidant defense and metabolites of glycolysis against the background of using statins in animals in the experiment for clarifying the diagnosis of statin-associated myopathy.Materials and methods. The study was conducted on outbred male rats, which were divided into 3 groups. The control group consisted of intact animals, and there were two experimental groups: group 1 – animals with induced hypercholesterolemia, group 2 – animals with induced  hypercholesterolemia treated with simvastatin. In the muscles of animals from the studied groups, the content of structural proteins of the sarcomere, titin and nebulin, was analyzed, and the concentration of glycolysis metabolites (pyruvic acid and lactate) and the activity of antioxidant defense enzymes (superoxide dismutase (SOD) and catalase) were determined.Results and discussion. The use of simvastatin in the animals led to a  decrease in the content of NT- and N2Atitin isoforms and an increase in the  content of the T2-proteolytic fragment. Complete absence of nebulin was also noted, which reflects the presence of dystrophic changes in the muscle  tissue. Long-term administration of simvastatin caused metabolic changes in the rats, characterized by impaired supply of cells with molecular oxygen. However, as opposed to the animals with hypercholesterolemia that were not given statins, a decrease in hypoxia-induced shifts was observed. Abnormalities in the performance of the antioxidant defense (AOD) system and multidirectional changes in the activity of the antioxidant pair “SOD –  catalase” were noted. The correlation analysis revealed a positive relationship between the content of the NT-titin isoform and the SOD activity and negative correlations between the content of the N2A-titin isoform and the level of lactate, as well as between the T2-proteolytic fragment of titin and the level of lactate.Conclusion. The study revealed a complex set of biochemical changes in the muscles that underlie myotoxicity of statins during their long-term use. Additional biochemical parameters were found – SOD activity and lactate concentration, changes in which, along with the determination of titin and  nebulin concentrations, indicating tissue hypoxia, will make it possible to more accurately diagnose statin-associated myopathy.